Razvoj zaživljenjske diagnostike bolezenskih beljakovinskih odlag v možganih: prionske bolezni - Šmid, Alojz (Zdravniški vestnik, 2011)
Translational medicine is a term describing systematic efforts for adequate testing and transfer of basic research findings into dinical practice. The paper outlines a series of studies aimed at evaluating adiagnostic potential of positron emission tomography with a radioisotope probe (18F)FDDNP for earlyrecognition of pathologic protein deposits in the brain s of prion disease patients. Slovene scientists contributed significantly to all studies in this bench-to-bedside sequence of translational neuroscience.
Keywords: amiloid; degenerativne bolezni; diagnostika; Methods; možgani; neurology; nevrologija; Prion Diseases; Prioni; Prions; Prionske bolezni; Tomografija emisijska-računalniška; Tomography, Emission-Computed